Practical and Metal-Free Electrophilic Aromatic Halogenation by Interhalogen Compounds Generated In Situ from N-Halosuccinimide and Catalytic TMSCl - Maibunkaew, Tapanee; Thongsornkleeb, Charnsak; Tummatorn, Jumreang; Bunrit, Anon; Ruchirawat, Somsak (Synlett, 2014)
Halomonochloride compounds (ClCl, BrCl, ICl) generated in situ from N-halosuccinimide and catalytic chlorotrimethylsilane (TMSCl, 0.1 equiv) can efficiently halogenate aromatic compounds to give halogenated products in good to excellent yields and selectivities. The reaction can be carried out at room temperature or at lower temperatures, requires only one hour, is practical to apply to a wide range of substrates, and provides a simple access to a variety of haloarene compounds.
Keywords: interhalogens; electrophilic aromatic halogenation; isocryptolepine; chlorotrimethylsilane; N-halosuccinimide